Self Disclosure Pengguna Aplikasi Kencan Online (Studi pada Tinder) - Cinintya Manu, Ni Putu; Sugiarica Joni, I Dewa Ayu; Purnawan, Ni Luh Ramaswati (E-Jurnal Medium; Vol 1 No 1 (2017), 2017)
The online dating application has changed the way people find a dating friend, from face-to-face into an online encounter. One of the online dating application is Tinder. Tinder users do an online interaction such as exchange personal information as a relationship development process, before they decide to meet face-to-face. One of the stages that influence the relationship development is self disclosure. Self disclosure is the way people disclose their personal information. In the online encounter, self disclosure happenes when someone disclose their personal information via internet to another person. The aim of this research is to explain self disclosure of the Tinder users. This research is qualitative research, using social penetration theory and CMC. The result of the study found that through 1 day-2 weeks self disclosure, the intensity of the six subjects are different, with a constant and stable intensity, someone can disclose their self better. With those different intensity, all subjects disclose their personality structure randomly. 3 of 6 subjects disclose their self till the third level (preference in something), subject D is the one who can disclose her self till the deepest level, but she didn’t pass the third and fifth level. The same background with her match make her do self disclosure till the sixth level. Personality structure those disclose randomly make an impact to the depth of self disclosure. 4 of 6 subjects can pass the second and third level of the depth self disclosure phase.   Keywords: Self Disclosure, Online Dating Application Users, Tinder